2011
DOI: 10.3390/ijms12084991
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects against 2-Bromopropane-Induced Apoptosis and Disruption of Embryonic Development in Blastocysts

Abstract: 2-Bromopropane (2-BP) is used as an alternative to ozone-depleting cleaning solvents. Previously, we reported that 2-BP has cytotoxic effects on mouse blastocysts and is associated with defects in subsequent development. In the present work, we show that 2-BP induces apoptosis in the inner cell mass of mouse blastocysts, and inhibits cell proliferation. Both effects are suppressed by resveratrol, a grape-derived phytoalexin with known antioxidant and anti-inflammatory properties. 2-BP-treated blastocysts displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As oxidative stress plays critical roles in the apoptosis triggered by a number of chemical compounds [ 35 , 36 , 37 , 38 , 39 , 40 ], we investigated whether reactive oxygen species (ROS) could be involved in the rhein-induced apoptosis of blastocysts in vitro. Staining with dichlorodihydrofluorescein diacetate (DCFDA) fluorescence dye (which detects intracellular ROS levels) revealed that the rhein-treated group had significantly higher ROS levels compared to the untreated control group ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…As oxidative stress plays critical roles in the apoptosis triggered by a number of chemical compounds [ 35 , 36 , 37 , 38 , 39 , 40 ], we investigated whether reactive oxygen species (ROS) could be involved in the rhein-induced apoptosis of blastocysts in vitro. Staining with dichlorodihydrofluorescein diacetate (DCFDA) fluorescence dye (which detects intracellular ROS levels) revealed that the rhein-treated group had significantly higher ROS levels compared to the untreated control group ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol (0.5 μM) can also protect against oxidative damage in preimplantation embryos (Chan, 2011) and improve porcine and bovine preimplantation embryo development in vitro (Lee, et al, 2010, Salzano, et al, 2014, Wang, et al, 2014). A natural flavonoid, quercetin, can protect embryos from peroxide induced damage (Yu, et al, 2014).…”
Section: Interventions To Reduce Impact Of Er Stress Responsementioning
confidence: 99%
“…In a study, blastocysts were exposed to 2‐bromopropane in which levels of implantation and ability to proceed to later stages of embryonic development were lowered. Moreover, 2‐bromopropane led to ROS production, loss of mitochondrial membrane potential, and activation of caspase 3, whereas RSV counteracted them (Chan, ).…”
Section: Chemical‐induced Toxicitymentioning
confidence: 99%